The effects of the processes of domesticating and applying international law in Malawi - Kondowe, Alexander Justice (Department of Public Law, 2022)
International law enjoys a considerable space in Malawi's domestic law as evidenced in several constitutional provisions that allow the application of international law in Malawi. While several constitutional provisions allow the application of international law in domestic law, the process of how international law forms part of the domestic law is provided under section 211 of the constitution of Malawi where it provides for instances of the direct and indirect application of treaties and CIL in Malawi's domestic law. This dissertation discusses the relationship between international law and domestic law in Malawi by analysing how the process of domesticating and applying international law in Malawi affects the development or growth of domestic law. Therefore, this dissertation answers the question of; to what extent is the process of domesticating and applying international law in Malawi affects the development of domestic law. To fully grasp the effects of domesticating and applying international law in Malawi, this dissertation will discuss the role and application of treaties and CIL in domestic law. It will be discussed that while some monist elements can be seen in the constitution, but the constitutional order and the courts agree that Malawi is predominantly a dualist state. The presence of the monist and dualist elements is an indication that changes in international law are likely to affect changes in domestic law through either the process of legislation by parliament interpretation of the law by courts. As a dualist state, the general position is that whenever a conflict arises between international law and domestic law, domestic law prevails. However, the courts as interpreters of the law in Malawi have taken a different approach of applying international law to the extent that they have consistently interpreted the law in a manner that avoids a conflict between international law and domestic law. It will be argued that the reason why the courts have developed a principle of avoiding a conflict between international law and domestic law is that the court as an arm of government is part of the government's efforts to fulfill its international obligations. Therefore, any attempt to invalidate such obligations in domestic law would be viewed that the government of Malawi is fighting itself. Therefore, whether the processes of transforming or incorporating international law into Malawi's domestic law is done through legislation or interpretation of the law by courts, it equally affects or influences changes or development of the domestic law in Malawi because whether it is legislation or courts decision, they are all binding law domestically.